Probability reasoning in judicial fact-finding. (January 2020) - Hunt, Ian; Mostyn, Justice
We argue that the laws of probability promote coherent fact-finding and avoid potentially unjust logical contradictions. But we do not argue that a probabilistic Bayesian approach is sufficient or even necessary for good fact-finding. First, we explain the use of probability reasoning in Re D (A Child) [2014] EWHC 121 (Fam) and Re L (A Child) [2017] EWHC 3707 (Fam). Then we criticise the attack on this probabilistic reasoning found in Re A (Children) [2018] EWCA Civ 1718, which is the appeal decision on Re L . We conclude that the attack is unjustified and that the probability statements in the two cases were both valid and useful. We also use probabilistic reasoning to enlighten legal principles related to inherent probability, the Binary Method and the blue bus paradox.